Investigating the Potential of Using Soya Beans Powder as a Natural Coagulant. - Imalingat, Gabriel (Kabale University, 2023)
This study investigates the potential of Soya beans powder as a natural coagulant for water treatment. This is aimed at identifying Soya beans powder as a possible replacement for alum and other chemical coagulants in treating water. Laboratory scale studies using jar test experiments were performed water collected from the sedimentation tank whose source was River Rwizi with detention time of 2 hrs. to determine the effect of varied dosages from 5mg/l to 30mg/l for both soya beans powder and alum on coagulation. The results showed that at dosage of 18.2 mg/l reduced turbidity to 3.4 NTU, color of 52 TCU, Electrical conductivity of 144.6 µS/cm, TDS of 70 mg/l, pH of 7.3 and TSS of 20mg/l which became the Optimum from the initial turbidity of 49.5 NTU, color of 470 TCU, Electrical conductivity of 153 µS/cm, TDS of 89 mg/l, pH of 7.49 and TSS of 50mg/l according to the WHO standards of drinking water, the turbidity is supposed to be between ranges of 5 NTU < 1 NTU, Electrical conductivity of < 1,400 μS/cm , TDS levels are below 300 mg/l which show excellent rating. The pH value is also within the acceptable limits of 6.5-8.5 < 8.0. WHO recommends maximum of 15 TCU, however the best colour removal was not up to the WHO recommended value of 15 TCU, when alum was used to treat the same water, it showed some good performance giving an optimum at dosage of 25mg/l with values of 1.2 NTU, 4 TCU, 229.1µS/cm, TDS of 45 mg/l, pH of 6.9 and finally TSS of 4mg/l. These values met the recommended WHO standards. The results above show that soya beans powder can be used to treat portable water at house hold level.